Pendidikan Kewarganegaraan di Tengah Tantangan Globalisasi - Vanny Permata Rinda; Dyana Sukma; Fikria Humaimah; Andi Mustika Rosa; Diva Rahdatul Hasnah; Alwi Sihab; Yofi Lasimta Mansur; Syukran Setiawan; Hambali Hambali (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
This article discusses how Civic Education can be a solution in facing the challenges of globalization, by instilling the values of Pancasila, love for the homeland, social responsibility, and strengthening national identity. The methods used are literature studies and qualitative analysis of various relevant sources. The results show that globalization brings a great challenge to Indonesia's national identity, especially among the younger generation. The flow of information and foreign culture that enters without borders can weaken the spirit of nationalism and local values such as mutual cooperation and tolerance. In this context, Civic Education (PKn) has a strategic role in building a strong national character and integrity. Emphasis on the importance of integrating national values in civil society is very important in forming a young generation that is resilient, critical, and ready to contribute to the global world without losing their identity as Indonesian citizens.